The Governance of International Migration - Üstübici, Aysen (Amsterdam University Press, 2018)
As concern about immigration has grown within Europe in recent years, the European Union has brought pressure to bear on countries that are allegedly not sufficiently governing irregular migration with and within their borders. This book looks at that issue in Turkey and Morocco, showing how it affects migrants in these territories, and how migrant illegality has been produced by law, practiced and negotiated by the state, other civil society actors, and by migrants themselves. Ayen Üstübici focuses on a number of different aspects of migrant illegality, such as experiences of deportation, participation in economic life, and access to health care and education, in order to reveal migrants' strategies and the various ways they seek to legitimise their stay.